Pengembangan Bakat Siswa Melalui Kegiatan Unjuk Kreasi - Navima Aulya Sava; Windasari Windasari; Amrozi Khamidi (Studia Manageria, 2023)
Every human being is born with talents according to their respective interests, so that the development of students in educational institutions is not only in the academic field, but in the development of talents. The teacher's role in developing student talents is to accommodate all forms of student talents, provide a place to accommodate student talents, and provide positive motivation to students. Data collection was carried out at SDN Singonegaran 1 Kediri with a qualitative method, namely by interviewing the person in charge of talent development activities. SDN Singnegara 1 Kediri has talent development activities, namely creative demonstration activities which are held every Saturday. Each class must perform one performance per week. Seen from every week, the enthusiasm of students is increasing, this is because the self-confidence of students has started to be high. The purpose of this activity is to accommodate and develop students' talents and interests, besides that this activity also aims to train students' self-confidence. Thus, this study aims to find out how educational institutions develop students' talents and interests, and this research will examine (1) program planning for creative demonstration activities at SDN Singonegaran 1 Kediri by setting all objectives for these activities, (2) Organizing in the implementation of creative demonstration activities at SDN Singonegaran 1 Kediri, (3) Actuating of implementing the creative demonstration activity program at SDN Singonegaran 1, (4) Controlling of activities carried out to evaluate program activities so that they continue to run according to the predetermined plan.